HOW JAMES JOYCE TRANSLATES HIMSELF - Senn, Fritz (Cahiers du Centre de Linguistique et des Sciences du Langage, 2013)
The article shows, in concrete examples, how Joyce’s works, in particular Ulysses and Finnegans Wake, do in fact translate some of their material internally. This does not only happen to foreign phrases when rendered into English, often with humorous side effects, but also on a large scale. It is characteristic of Joyce’s Ulysses that it metamorphoses itself into various distinct shapes, styles, modes, perspectives that are often magnified into parodies, so that almost each episode is highly idiosyncratic and so easily identifiable. The double nature of the English vocabulary (basic Germanic elements alongside those derived from Latin) is exploited to the utmost. Joyce also highlights the Gaelic substratum that shows in the elaborate use of Hiberno-English. Finnegans Wake obviously translates its own features at almost every turn and so expands linguistic borders. Certain phrases and passages, moreover, can literally be read or heard as English as well as French, German, Spanish or more remote languages. In his multiple transformations Joyce may well be the most Irish of all writers as well as the least Irish and most cosmopolitan